Efektivitas Program Asuransi Ketenagakerjaan BPJS Ketenagakerjaan dalam Meningkatkan Kesejahteraan Pekerja Formal dan Informal di Indonesia - Mega Lenita Purnama; Mutiara Zahra Bilqis; Muhamad Syahwildan (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
Employment insurance is an important instrument in the social protection of workers. In Indonesia, BPJS Ketenagakerjaan has launched various insurance programs, including JKK, JKM, JHT, and JKP. However, the effectiveness of these programs in improving the welfare of workers, especially the informal sector which accounts for more than 59% of the workforce, remains a question. This study uses a quantitative approach with descriptive and linear regression methods on secondary data from BPJS and BPS for the last five years. The results show that there is an imbalance in participation between the formal and informal sectors due to low literacy and limited regulations. This research produces a databased participatory recommendation model to improve the effectiveness of the BPJS Ketenagakerjaan program and encourage social inclusion for all workers.